2018
DOI: 10.1021/acs.jpcc.8b09665
|View full text |Cite
|
Sign up to set email alerts
|

Charge Mobility and Recombination Mechanisms in Tellurium van der Waals Solid

Abstract: Trigonal tellurium is a small band gap elemental semiconductor consisting of van der Waals bound one-dimensional helical chains of tellurium atoms. We study the temperature dependence of the charge carrier mobility and recombination pathways in bulk tellurium. Electrons and holes are generated by irradiation of the sample with 3 MeV electrons and detected by time-resolved microwave conductivity measurements. A theoretical model is used to explain the experimental observations for different charge densities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 52 publications
0
24
1
Order By: Relevance
“…The radiative recombination coefficient was obtained as 1.9 ∓ 0.1 × 10 −9 cm 3 /s. Our value is lower than the 1.1 × 10 −8 cm 3 /s obtained by Bhaskar et al [44] but higher than other traditional direct-band-gap semiconductors such as GaAs, which has a value of ∼7 × 10 −10 cm 3 /s at room temperature. The surface recombination velocity is found as V s = 2×10 6 t cm/s, where t is the thickness in nanometers.…”
contrasting
confidence: 73%
See 2 more Smart Citations
“…The radiative recombination coefficient was obtained as 1.9 ∓ 0.1 × 10 −9 cm 3 /s. Our value is lower than the 1.1 × 10 −8 cm 3 /s obtained by Bhaskar et al [44] but higher than other traditional direct-band-gap semiconductors such as GaAs, which has a value of ∼7 × 10 −10 cm 3 /s at room temperature. The surface recombination velocity is found as V s = 2×10 6 t cm/s, where t is the thickness in nanometers.…”
contrasting
confidence: 73%
“…The transmission electron microscopy (TEM) cross section of the flakes in a previous study revealed good quality of the flakes in the bulk, and hence point defects and dislocations are less likely [20]. Therefore, radiative or SRH (Shockley-Read-Hall, trapassisted) recombination are the more probable recombination routes, as was also deduced in a recent study on recombination dynamics in powdered tellurium [44]. Moreover, the authors found that radiative recombination is dominant with 98% radiative yield at room temperature.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…However, the LP orbitals overlap the antibonding (σ*) orbitals on adjacent chains. It has been pointed out that the overlap between LP and σ* orbitals through chains is the cause of the interchain interactions. , However, in many studies, interchain interactions have been thought to be van der Waals interactions. The 1NN atomic distances between the chains are 3.467 and 3.478 Å for t-Se and t-Te, respectively, which are clearly smaller than twice the van der Waals radii, that is, 1.9 and 2.1 Å, respectively . The van der Waals interaction originates from dipole–dipole interactions and is thus weak.…”
Section: Introductionmentioning
confidence: 99%
“…The yellowish translucent flakes of SnS 2 were filled into a polyetheretherketone (PEEK) sample holder with a groove of 1 mm along the direction of high-energy electron irradiation, analogous to our previous study on Te. 30 The flakes were tightly pressed to fill the groove entirely. The sample holder was inserted into a copper waveguide cell suitable to perform microwave conductivity studies in the K aband (28−37 GHz), similar to previous studies.…”
Section: ■ Introductionmentioning
confidence: 99%